Contribution of Trigona Honey Bee Business (Trigona sp) to Farmers' Income in Bengkaung Village, West Lombok Regency - Ramdiawan, Ramdiawan; Herdiana, Herdiana; Rosadi, Narita Amni (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2023)
The research was conducted in Bengkaung Village, Batu Layar District, West Lombok Regency with the aim of finding out farmers' income from Trigona Honey Bee (Trigona sp.) cultivation and plantation farming as well as analyzing the contribution of Trigona Honey Bee cultivation to the total of farmers' income. The research uses primary data and secondary data. Primary data was obtained from interviews with farmers, while secondary data was obtained from related agencies. The number of respondents was 36 farmers. The data analysis took the form of income analysis, cost analysis and analysis of the percentage of contribution of the Trigona Honey Bee cultivation business to the total of farmers' income. The results show that the average annual income of farmers from the Trigona Honey Bee cultivation business is IDR. 15,162,075 while the average total income of farmers per year is IDR. 35,914,739 which means the contribution of the Trigona Honey Bee Cultivation is 42%. Meanwhile, the obstacles faced in cultivating Trigona Honey Bee are the shortages of bee's food during the rainy season, predator interference, lack of post-harvest knowledge which causes the queen of the bee to die during the harvesting process and the farmers' ignorance of good honey harvest times.